IMPLEMENTATION OF SOCIAL MORALS AND RESPONSIBLE ATTITUDES IN FORMING STUDENTS' DISCIPLINED CHARACTER IN MADRASAH IBTIDAIYAH - Darotul Zuhro, Faizah; M. Samsul Hady; Muh. Hambali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education plays a vital role in shaping students’ personalities in Islamic elementary schools (Madrasah Ibtidaiyah). This study aims to analyze the implementation of social morals in fostering discipline among students at the Madrasah Ibtidaiyah level. The research employs a descriptive qualitative method, with data collected through observation, interviews, and documentation. Findings indicate that consistent application of social morals through daily routines, learning activities, and responsibility cultivation enhances students’ discipline and awareness of school norms and rules. These results highlight that strengthening students’ disciplined character is most effective when social morals are developed continuously.